Overreaction of syariah stocks: does size matter? - Ali, Norli; Abd. Talib, Norli; Md Nasir, Annuar; Zainal Abidin, Sazali (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
The purpose of the study is to investigate stock overreaction behavior among syariah stocks in Bursa Malaysia using basic framework of De Bondt and Thaler (1985). Like its conventional counterpart, evidence of stock overreaction behavior is also observed in syariah compliant stocks in Malaysia. The study documents that both winner and loser portfolios experience reversal behavior even after adjustment for size, thus implies that size does not matter. Furthermore, after adjustment for size, loser portfolios outperform winner portfolios in the test period. This indicates that syariah compliant stocks in Malaysia also provide opportunity of earning abnormal profit by resorting to contrarian strategy.